Efficiency in education: primary and secondary schools in Italian regions. Issue 10 (3rd October 2022) - Chiariello, Valentina; Rotondo, Francesca; Scalera, Domenico
ABSTRACT: By using stochastic frontier analysis, single- and multiple-output methods, this paper empirically investigates the efficiency of Italian regions in providing public primary and secondary education for the period 2011–18. The analysis detects strong interregional differences, outlining a clear North–South geographical pattern. To single out the reasons for the poor performance of Southern regions, context variables (per capita gross domestic product, poverty, institutional quality, adult education) are considered and shown to be highly relevant in shaping regional efficiency. Finally, when interregional disparities in socio-economic factors are accounted for, no residual geographical pattern in regional efficiency emerges.